A case of osteomalacia due to deranged mineral balance caused by saccharated ferric oxide and short-bowel syndrome: A case report. Issue 39 (September 2017) - Nomoto, Hiroshi; Miyoshi, Hideaki; Nakamura, Akinobu; Nagai, So; Kitao, Naoyuki; Shimizu, Chikara; Atsumi, Tatsuya
Abstract: Rationale: Saccharated ferric oxide has been shown to lead to elevation of fibroblast growth factor 23, hypophosphatemia, and, consequently, osteomalacia. Moreover, mineral imbalance is often observed in patients with short-bowel syndrome to some degree. Patient concerns: A 62-year-old woman with short-bowel syndrome related with multiple resections of small intestines due to Crohn disease received regular intravenous administration of saccharated ferric oxide. Over the course of treatment, she was diagnosed with tetany, which was attributed to hypocalcemia. Additional assessments of the patient revealed not only hypocalcemia, but also hypophosphatemia, hypomagnesemia, osteomalacia, and a high concentration of fibroblast growth factor 23 (314 pg/mL). Diagnoses: We diagnosed her with mineral imbalance-induced osteomalacia due to saccharated ferric oxide and short-bowel syndrome. Interventions: Magnesium replacement therapy and discontinuation of saccharated ferric oxide alone. Outcomes: These treatments were able to normalize her serum mineral levels and increase her bone mineral density. Lessons: This case suggests that adequate evaluation of serum minerals, including phosphate and magnesium, during saccharated ferric oxide administration may be necessary, especially in patients with short-bowel syndrome.